2016
DOI: 10.1371/journal.pone.0153608
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Chronic Neuropathological and Biochemical Changes in Mouse Visual System after Repetitive Mild Traumatic Brain Injury

Abstract: Repetitive mild traumatic brain injury (r-mTBI) results in neuropathological and biochemical consequences in the human visual system. Using a recently developed mouse model of r-mTBI, with control mice receiving repetitive anesthesia alone (r-sham) we assessed the effects on the retina and optic nerve using histology, immunohistochemistry, proteomic and lipidomic analyses at 3 weeks post injury. Retina tissue was used to determine retinal ganglion cell (RGC) number, while optic nerve tissue was examined for ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 91 publications
6
44
0
Order By: Relevance
“…[46][47][48][49][50] LysoPC levels are drastically elevated in patients with brain injury. [51] COX-2 is widely involved in brain trauma, ischemia-induced neuronal damage, inflammatory responses, and neurodegenerative diseases. The role of COX-2 in neuropathology is related to changes JIA ET AL.…”
Section: The Third Pathway Involves the Effect Of Quercetin On Cadmmentioning
confidence: 99%
“…[46][47][48][49][50] LysoPC levels are drastically elevated in patients with brain injury. [51] COX-2 is widely involved in brain trauma, ischemia-induced neuronal damage, inflammatory responses, and neurodegenerative diseases. The role of COX-2 in neuropathology is related to changes JIA ET AL.…”
Section: The Third Pathway Involves the Effect Of Quercetin On Cadmmentioning
confidence: 99%
“…Intriguing, in this context, is the impaired phosphorylation of AKT and, therefore, loss of inhibitory phosphorylation of GSK 3b observed in the PNS of plasmalogen-deficient mice [59]. GSK 3b is one of the kinases implicated in tau phosphorylation [217]; and increased GSK 3b activity upon plasmalogen deficiency may well contribute to Increased levels of some ether-bonded species, particularly such with choline head groups in murine optic nerve after repetitive mild traumatic brain injury [262] Reduced PlsEtn levels in spinal cord after laminectomy and spinal cord compression in a cat model [263] Spinal cord ischemia Reduction of PlsEtn levels (and other ethanolamine phospholipids) in spinal cord of rabbits after ischemia [264] Ischemic stroke Reduction of PlsEtn levels in synaptosomes from rat striatum after injection of endothelin-1 (producing an ischemia-like lesion) [265] Increased levels of PAF in blood of patients [266] Correlation between PAF binding to platelets and infarct volume as well as neurological outcome [267] APLP, amyloid precursor protein-like protein; MPTP, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridin; MS, multiple sclerosis; PS, presenilin.…”
Section: Disease Reported Involvement Of Ether Lipidsmentioning
confidence: 99%
“…Some proteins identified in our study were previously identified as upregulated in a proteomic analysis of optic nerves from mice subjected to repetitive blunt impact TBI [59]. These proteins included ALB, MAP1A, and TUBA4A.…”
Section: Discussionmentioning
confidence: 54%
“…Visual dysfunction can be observed immediately following injury [56], with deficits persisting months after the injury [57]. The visual system damage observed after blast exposure is similar to damage observed in weight drop models of TBI [52,58,59], suggesting similar mechanisms. These mechanisms are varied and include axonal damage, activation of microglia, tissue swelling, infiltration of immune cells, upregulation of chemoattractants, and neuroinflammation [8,60,61,62,63,64,65,66,67].…”
Section: Discussionmentioning
confidence: 63%